PENGARUH KEAKTIFAN BERORGANISASI DAN KOMUNIKASI INTERPERSONAL TERHADAP PRESTASI BELAJAR ILMU ORGANISASI MAHASISWA PAP FKIP UNS - Muhammad Zainuddin; Hery Sawiji; Tri Murwaningsih (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
The research uses quantitative descriptive methods. The respondents of this study were students of 2015-2017 PAP FKIP UNS Surakarta who received organizational science courses of 203 students. The sampling technique used was Proportional random sampling with a sample of 135 students. Data collection techniques used were questionnaires and documentation. Questionnaires are used to collect data on activeness in organizing and interpersonal communication, while documentation is used to collect data on learning achievement in organizational science courses. The data analysis technique used is multiple regression analysis.The results of this study are: (1) There is a significant effect of organizational activeness on the academic achievement of the 2015-2017 PAP FKIP UNS Surakarta as indicated by the t count value of the organizational activeness variable is 3,819 > t table is 1,978 and sig. 0,000 < 0,05. (2) There is a significant influence on the activeness of organizing on the learning achievement of the 2015-2017 PAP FKIP UNS Surakarta as indicated by the count value of interpersonal communication is 8,121 > t table is 1,978 and the value of sig. 0,000 < 0,05. (3) There is a significant influence on the activeness of organizing and interpersonal communication together on the learning achievement of the 2015-2017 PAP FKIP UNS Surakarta as indicated by F count value greater than F table, which is 129,660 > 3,06